Mean Platelet Volume and Related Factors in Patients at Different Stages of Diabetic Nephropathy: A Preliminary Study. (March 2014) - Turgutalp, Kenan; Özhan, Onur; Akbay, Esen; Tombak, Anıl; Tiftik, Naci; Ozcan, Turkay; Yılmaz, Sercan; Helvacı, İlter and Kiykim, Ahmet
Introduction: Mean platelet volume (MPV) is an independent cardiovascular disease predictor, and characteristics of MPV in patients with diabetic nephropathy (DN) are not well known. Aim: To determine the MPV levels in patients at different stages of DN. Patients and Methods: The MPV levels were investigated in healthy participants (group 1, n = 157), patients with type 2 diabetes mellitus without complication (group 2, n = 160), diabetic patients with clinical proteinuria (group 3, n = 144), and in patients with chronic kidney disease due to DN (group 4, n = 160). Findings: The MPV level was higher in all diabetic patients than that in normal participants ( P < .05). The MPV values had a positive correlation with the serum creatinine and proteinuria, and a negative correlation with the glomerular filtration rate ([GFR] P < .001 for all, r values; .72, and .82, and −.92, respectively). Conclusion: The MPV values were higher in diabetic groups than that in normal participants. Both GFR and proteinuria were the most powerful determinants of MPV.